PENGARUH BEBAN KERJA, STRES KERJA, DAN LINGKUNGAN KERJA TERHADAP TURNOVER INTENTION PADA PT ENAM TIGA SEJAHTERA - Trisnadewi, Ni Kadek Ayu; Ardani, Ni Kadek Mely (Jurnal Daya Saing, 2023)
The purpose of this study are to know the effect of workload, work stress and work environmenton turnover intention at PT Enam Tiga Sejahtera. The data analysis technique used in this study isStructural Equation Modeling (SEM) based on variance SEM, which is well known as the Partial LeastSquare (PLS) visual version 3.0. The result of this study indicate that the relationship between workload andturnover intention shows a path coefficient value of 0.233 with a t-statistic value 0f 2.348 which is greaterthan t table (1.960). The relationship between work stress and turnover intention shows a path coefficientvalue of 0.450 with a t-statistic value of 4.128 which is greater than t table (1.960). The relationshipbetween work environment variables and turnover intention shows a path coefficient value of -0.291 with at-statistic value of 2.915 which is greater than t table (1.960).